2010
DOI: 10.1149/1.3485039
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Field Emission Device from a Spray Coating of Single-Wall Carbon Nanotubes

Abstract: A transparent field emission device made from spray coating a single-wall carbon nanotube ͑SWNT͒ in N,N-dimethylformamide ͑DMF͒ was developed. Highly crystalline SWNTs were successfully synthesized using a vapor phase method. Amorphous carbon and catalyst metal particles that remained in the SWNTs were removed using a purification process. The purified SWNTs were diluted and dispersed in DMF using an ultrasonic bath and a magnetic stirrer. The residue was removed by centrifugation of the SWNT DMF solution. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Peaks corresponding to bulk In in the 3d region were assigned at 444.0 eV (3d5/2) and at 451.5 eV (3d3/2). The bulk In 3d5/2 peak has been assigned previously at 444.4 eV in InGaAs, although several inconsistencies in the position of this peak are possible due to the presence of In oxides and metallic In, and due to the As content if an As core level has been used to compensate for charging correction (9). The reference position for In2O3 was set at 452.1 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peaks corresponding to bulk In in the 3d region were assigned at 444.0 eV (3d5/2) and at 451.5 eV (3d3/2). The bulk In 3d5/2 peak has been assigned previously at 444.4 eV in InGaAs, although several inconsistencies in the position of this peak are possible due to the presence of In oxides and metallic In, and due to the As content if an As core level has been used to compensate for charging correction (9). The reference position for In2O3 was set at 452.1 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Wet etching in HCl, HF, and H2SO4 has been used to remove the surface oxides on In0.53Ga0.47(100), leaving an As rich surface (8). To reduce the interface defects and Fermi level pinning in metal-oxide-semiconductor field effect transistor (MOSFET) devices, surface passivation with phosphorous nitride was used to reduce the frequency dispersion by ~90% compared to a non-passivated device (9). Devices fabricated with In0.53Ga0.47(111) substrates cleaned in dilute HCl and treated with ammonium sulfide, (NH4)2S, had a higher channel mobility than the (100) counterpart, and showed a 100% improvement with respect to the Si channel at high surface carrier concentration (4).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the stability of the emission current must be ensured during a long-term operation. Here, CNTs can be prepared on various types of substrates such as flat types and tip types either by direct [ 4 - 6 ] or indirect [ 7 - 10 ] methods. Practically, the indirect methods have certain advantages over the direct methods due to their simpler deposition systems, lower costs, lower processing temperatures, and easier scale-up.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their remarkable emission stability and mechanical strength, [1,2] carbon nanotubes (CNTs) have been applied in field emission display devices and molecular sensors. [3,4] Among these applications, one of the core problems is how to produce lower threshold voltage and stronger field emission current at low electric field strength. [5] Previous studies have shown that tuning the structures, such as the radius, [6] geometry, [7−10] packing density, [11,12] and polar molecule adsorption, [13−15] is the most common and effective way to improve the field emission performance of CNT systems.…”
Section: Introductionmentioning
confidence: 99%